Construction of an easily detectable transgenic Synechococcus elongatus PCC 7942 against White Spot Syndrome Virus using vp28 and mOrange Gene and its metabolism in shrimp - Peng, Wen; Bao, Qunjing; Jia, Rui; He, Peimin (Frontiers in Immunology, 2022)
White spot syndrome is an epidemic disease caused by the highly contagious and lethal white spot syndrome virus (WSSV), resulting in huge economic losses to the global aquaculture industry. VP28 is the main structural protein in the capsule of WSSV and is important in the early stage of infection. Under an excitation wavelength of 548 nm, the mOrange fluorescent protein releases a 562 nm emission wavelength, which is different from the autofluorescence of cyanobacteria. Therefore, using this characteristic combined with the receptor system of Synechococcus elongatus PCC 7942, we constructed transgenic S. elongatus to express the recombinant protein VP28-mOrange. In addition, PCR and western blotting were used to confirm the stable expression of the target gene in cyanobacteria. Using mOrange tracer features, we explored the recombinant protein VP28-mOrange in the metabolic cycle of young Litopenaeus Vannamei after feeding. After the young shrimp had stopped consuming transgenic cyanobacteria, the 24 to 33 h fluorescence signal in the intestine was very weak, and almost disappeared after 36 h. We explored the protective effect of transgenic vp28-mOrange S. elongatus within 48 h of being ingested by L. vannamei and set WSSV challenges at 2, 12, 24, and 48 h post-immunization. However, the survival rate of L. vannamei decreased as the time of the WSSV challenge increased. The survival rate on the seventh day was 81%, 52%, 45.5%, and 33.3% for shrimps challenged for 2, 12, 24, and 48 h, respectively. Enzyme activity can also support this conjecture, the enzyme activity indexes of the experimental groups were significantly reduced compared to positive and wild-type controls. Therefore, this immune agent functioned as a preventive agent. Compared with the traditional method, this method was easy to detect and can visualize the digestion of transgenic cyanobacteria in the Litopenaeus vannamei intestine.